2009
DOI: 10.1021/jp808890x
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Hydrogen Storage in Zeolite-Templated Carbon

Abstract: High-pressure hydrogen storage in zeolite-templated carbon (ZTC) was investigated at room temperature (30 °C). Several types of ZTCs with different surface areas and a nitrogen-doped ZTC were prepared. Their hydrogen storage performance at room temperature was examined and the results were compared with those of commercial activated carbons. At pressures below 10 MPa, the hydrogen uptake capacity was simply proportional to specific surface areas of the carbons, and both ZTCs and activated carbon showed almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 40 publications
12
169
2
1
Order By: Relevance
“…At 6.7 MPa, hydrogen uptake in MSC-30 was 3.1 mmol g -1 , consistent with reported values for MSC-30 to within 0.3 mmol g -1 . 65,66 This value was reproducible upon cycling to well within experimental error, to which we assign an upper bound of ±0.05 mmol g -1 . In Pt-MSC-30, low-pressure data showed a steep initial uptake of hydrogen between 0-0.01 MPa and then a similar constant slope region to MSC-30 between 0.04-2 MPa.…”
Section: Hydrogen Sorption Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…At 6.7 MPa, hydrogen uptake in MSC-30 was 3.1 mmol g -1 , consistent with reported values for MSC-30 to within 0.3 mmol g -1 . 65,66 This value was reproducible upon cycling to well within experimental error, to which we assign an upper bound of ±0.05 mmol g -1 . In Pt-MSC-30, low-pressure data showed a steep initial uptake of hydrogen between 0-0.01 MPa and then a similar constant slope region to MSC-30 between 0.04-2 MPa.…”
Section: Hydrogen Sorption Resultssupporting
confidence: 60%
“…Template carbonization, among other methods of structural control, has also been explored as a technique to produce carbonaceous materials with exceptionally large specific surface area and finely tuned porosity 120,121,122,123,124,125,126,127 . It was reported in 2009 that a particular class of templated materials, zeolite-templated carbons (ZTCs), exhibits remarkable hydrogen storage capacities at room temperature under high-pressure conditions (10-34 MPa) 122 .…”
Section: Zeolite-templated Carbonsmentioning
confidence: 99%
“…Among others, they are of interest for increasing the electrochemical activity of carbon materials in the oxygen reduction reaction [7], [8]; for increasing the capacitance, rate performance and durability as electrodes of supercapacitors [9]- [11]; for enhancement of gas and liquid adsorption of acid adsorbates [12]; for the preparation of novel heterogeneous catalysts [13], [14] and for the immobilization of bio-molecules [15]. The synthesis of Ncontaining ZTC is done using chemical vapor deposition during its synthesis with which Nspecies are incorporated in the carbon network [16]- [20]; however, it is not possible to control the type of N-species and it inevitably becomes diverse. Post-synthesis modification without structure destruction of ZTC would be a highly desirable method for selective introduction of specific N-containing functional groups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…4 In summary, it was found that ZTC-3 has chemical properties similar to other ZTCs (being predominantly sp 2 hybridized carbon) and has very high template fidelity, having the structural traits of the best reported examples. 5,6 Its hydrogen adsorption properties are among the highest of reported carbonaceous materials, but are proportional to surface area between 77-298 K as for other carbons. The narrow pore-size distribution centered at 1.2 nm is not optimized for hydrogen adsorption.…”
Section: S3 II Materials Propertiesmentioning
confidence: 99%
“…The pore-size distribution (left) and relative filling (right) of CNS-201 (black), MSC-30 (red), ZTC "P7(2)-H" (blue), and ZTC-3 (purple), calculated by the NLDFT method. 4,5,9,10 It has been proposed that 1.14 nm is the optimal spacing between graphene layers for maximum adsorption uptake of methane. 11,12 The pore-size distribution of ZTC-3 has a mean pore-width close to this value, shown as a gray line in Figure S1.…”
Section: Dft Pore-size Comparisonmentioning
confidence: 99%